The Yoruba Philosophy of Law and the Challenge of Corruption in Nigeria - Aina, Adebayo A.; Akintona, Emmanuel Ola (NIU Journal of Humanities, 2019)
One of the challenges confronting nation-building in Africa today is the incessant destructive social forces and corruption in particular. The mechanism of accountability and transparency has been perverted not only by managers of governance, but by anti-corruption agencies. For example, the penal codes in Nigeria had become inertial as anti-corruption agencies could not match word with evolving criminality, and the judiciary who supposed to be the last hope of the masses, had become unreliable. The article shall adopt the conceptual, analytic and evaluative methods to examine corruption in the Nigeria system of government and see how the Yoruba philosophy of law could resolve some of the impending problems associated with it. The Yoruba philosophy of law is enriched with moral rectitude (Iwa) and integrity (omoluwabi); it provokes reformative mindsets from time to time in order to achieve and maintain social equilibrium. The article concludes that the embellished moral content of the Yoruba philosophy of law outwit the Western mainstream legal system; hence, adopting it will go a long way in solving the perennial problem of corruption in Africa and Nigeria in particular. Keywords:       Africa, Corruption, Governance, Morality, Philosophy of law, Yoruba